Seedling forage nutrition and spatial patterns of large prey mammals of tigers in Dong Phayayen-Khao Yai Forest Complex, Thailand - Wongbundit, Nithiporn; Paansri, Paanwaris; Suksavate, Warong; Chaiyes, Aingorn; Chanteap, Prawatsart; Duengkae, Prateep; Ngernsaengsaruay, Chatchai (Agriculture and Natural Resources, 2022)
Importance of the work: Forage seedlings as alternative food resources based on their nutrition are important for large prey mammals of tigers, instead of grasses. Objectives: To examine the nutritional value of predicted potential habitat area based on forage seedling species. Materials & Methods: Field data of seedlings were collected from 150 sampling points (1,822 sub-plots) during August 2019–March 2021, focusing on gaur (Bos gaurus) and sambar deer (Rusa unicolor) because they are the large prey mammals (> 100 kg) of tigers in Dong Phayayen-Khao Yai Forest. Results: In total, 13 species of seedlings were identified that were forage for the large prey mammals of tigers. Applying an electivity index to the large prey mammals of tigers showed that Irvingia malayana and Micromelum minutum had an exclusive electivity index. The Mun Sam Ngam area had the maximum potential for the effective management of forage seedlings. Main finding: The prediction of potential of habitat for most selected seedling species could be very useful for habitat improvement and population augmentation of gaur and sambar deer.